Smaller spared subcortical nuclei are associated with worse post-stroke sensorimotor outcomes in 28 cohorts worldwide. Issue 4 (27th October 2021) - Liew, Sook-Lei; Zavaliangos-Petropulu, Artemis; Schweighofer, Nicolas; Jahanshad, Neda; Lang, Catherine E; Lohse, Keith R; Banaj, Nerisa; Barisano, Giuseppe; Baugh, Lee A; Bhattacharya, Anup K; Bigjahan, Bavrina; Borich, Michael R; et al.
Abstract: Up to two-thirds of stroke survivors experience persistent sensorimotor impairments. Recovery relies on the integrity of spared brain areas to compensate for damaged tissue. Deep grey matter structures play a critical role in the control and regulation of sensorimotor circuits. The goal of this work is to identify associations between volumes of spared subcortical nuclei and sensorimotor behaviour at different timepoints after stroke. We pooled high-resolution T1 -weighted MRI brain scans and behavioural data in 828 individuals with unilateral stroke from 28 cohorts worldwide. Cross-sectional analyses using linear mixed-effects models related post-stroke sensorimotor behaviour to non-lesioned subcortical volumes (Bonferroni-corrected, P  < 0.004). We tested subacute (≤90 days) and chronic (≥180 days) stroke subgroups separately, with exploratory analyses in early stroke (≤21 days) and across all time. Sub-analyses in chronic stroke were also performed based on class of sensorimotor deficits (impairment, activity limitations) and side of lesioned hemisphere. Worse sensorimotor behaviour was associated with a smaller ipsilesional thalamic volume in both early ( n  = 179; d  =   0.68) and subacute ( n  = 274, d  =   0.46) stroke. In chronic stroke ( n  = 404), worse sensorimotor behaviour was associated with smaller ipsilesional putamen ( d  =   0.52) and nucleus accumbens ( d  =   0.39) volumes, and a larger ipsilesional lateral ventricle ( d  =   −0.42). Worse chronic sensorimotor impairment specifically (measured by the Fugl-Meyer Assessment; n  = 256) was associated with smaller ipsilesional putamen ( d  =   0.72) and larger lateral ventricle ( d  = −0.41) volumes, while several measures of activity limitations ( n  = 116) showed no significant relationships. In the full cohort across all time ( n  = 828), sensorimotor behaviour was associated with the volumes of the ipsilesional nucleus accumbens ( d  =   0.23), putamen ( d  =   0.33), thalamus ( d  =   0.33) and lateral ventricle ( d  = −0.23). We demonstrate significant relationships between post-stroke sensorimotor behaviour and reduced volumes of deep grey matter structures that were spared by stroke, which differ by time and class of sensorimotor measure. These findings provide additional insight into how different cortico-thalamo-striatal circuits support post-stroke sensorimotor outcomes. Abstract : Liew et al. report the first large-scale examination using high-resolution neuroimaging of subcortical nuclei and sensorimotor behaviour in 828 stroke patients from 28 cohorts worldwide. They discovered novel associations between post-stroke sensorimotor behaviour and specific subcortical nuclei, providing new insight for stroke rehabilitation. Graphical Abstract: